Promoting resource stewardship: Reducing inappropriate free thyroid hormone testing. Issue 3 (14th March 2017) - Gilmour, Julie A.; Weisman, Alanna; Orlov, Steven; Goldberg, Robert J.; Goldberg, Alyse; Baranek, Hayley; Mukerji, Geetha
Abstract: Rationale: Free thyroxine (fT4) and free triiodothyronine (fT3) tests are often ordered when not clinically warranted. Preventing laboratory overuse by reducing inappropriate fT4 and fT3 testing is one strategy to promote resource stewardship. Objectives: (1) To characterize the frequency of inappropriate fT4 and fT3 testing and (2) to implement a quality improvement strategy aimed at reducing the number of these tests performed. Methods: Quality improvement tools were used to create sequential change ideas: (1) education of physicians regarding appropriate indications for ordering fT4/fT3 and (2) implementation of a hospital‐wide laboratory and forced‐function system with a reflex fT4. This study was conducted at an academic ambulatory care hospital in Toronto, Canada. The main outcomes were the differences in weekly median number of thyroid‐stimulating hormone, fT4, and fT3 tests performed during the preintervention, education, and reflex periods using the Kruskal‐Wallis test and analysis for special cause variation with statistical process control charts. Results: The median number of fT4/fT3 processed per week was significantly reduced from 90/39 at baseline to 78/34 posteducation and 59/14 postreflex ( P < .0001). Comparing preintervention to the reflex period, there was 34% reduction in fT4 and 64% reduction in fT3. The number of processed thyroid‐stimulating hormone tests was stable with only 2% variation. Statistical process control charts demonstrated special cause variation following implementation of the reflex system for both fT4 and fT3. Conclusions and Relevance: Inappropriate testing of free thyroid indices occurs frequently. The implementation of a reflex fT4 strategy after education was feasible in reducing overall testing by 49% and was effective in promoting resource stewardship.